Effects of Strain‐Induced Cyclic Transformation on the Microstructure of the Peened Surface of SUS 304 Austenitic Stainless Steel. Issue 9 (21st August 2022) - Nakagawara, Yuji; Sato, Hisashi; Moritani, Tomokazu; Watanabe, Yoshimi
Abstract : The effects of strain‐induced cyclic transformation on surface microstructure are investigated for SUS 304 austenitic stainless steel. The strain‐induced cyclic transformation comprises the repetition of the strain‐induced martensitic transformation and the strain‐induced reverse transformation. Herein, the strain‐induced cyclic transformation is performed by the repetition of shot‐peening (SP) tests at room temperature and at 200 °C. SP at room temperature effects a martensitic transformation, whereas the reverse transformation, from martensite to austenite, is induced by SP at 200 °C. Compared with that of a specimen treated by conventional SP, the surface hardness of a specimen treated by strain‐induced cyclic transformation using SP is higher, because the dislocation density on the peened surface increases and the microstructure is refined. Therefore, the strain‐induced cyclic transformation affected by SP can enhance the surface mechanical properties of steels. Abstract : Strain‐induced cyclic transformation using shot‐peening (SP) is proposed as a novel method to enhance mechanical properties. This method is performed by repetition of strain‐induced martensitic transformation and strain‐induced reverse transformation induced by SP. The surface hardness of austenitic stainless steel is improved by this method due to introduction of fine grains, high dislocation density, and large compressive residual stress.